Beyond Broadband Access : Developing Data-Based Information Policy Strategies - Schejter, Amit M.; Taylor, Richard Denny (Book collections on Project MUSE., 2013)
This volume not only examines traditional questions about broadband, such as availability and access, but also explores and evaluates new metrics that are more applicable to the evolving technologies of information access. Importantly, the book provides a well-rounded, international perspective on theoretical approaches to communications policymaking in the Americas, Europe, Asia, and Africa. Showcasing a diversity of approaches, this collection aims to help meet the myriad challenges involved in improving the development of communications policy around the world.